Implementation of the Istishna' Contract in BTN Syariah Surabaya's Indent IB Mortgage Financing - Dila Iska Ariyanti; Mashudi (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
The dense population in Indonesia makes the housing needs of each individual with ease of ownership an opportunity for Islamic banks in marketing their mortgage products. This study aims to determine the implementation of the Istishna contract in financing the Indent Ib Mortgage Bank BTN Syariah Surabaya. Methods used Qualitative research on library studies (Library Researc) with data collection techniques through interviews with staff of Bank BTN Syariah Surabaya. In mortgage financing, Indent Ib uses an istishna contract, the realization of funding is divided into stages. The first stage is 40% for the work on the house foundation, the second stage is 40% for the work on the roof cover, the third stage is 10% for the completion of the house construction and the fourth level is 10% for the issuance of IMB and Certificates.